ISSUES OF IMPROVEMENT OF THE CITY OF KHIVA IN THE SOVIET PERIOD (EXAMPLE OF 1930-1950) (TAMADDUN NURI JURNALI, 2025)
This article analyzes the author’s achievements and shortcomings in the allocation of state funds for the improvement and landscaping of the city of Khiva during the Soviet era, changes in the appearance of the city, the construction of a power plant, increased attention to urban cleanliness, and the establishment of a water supply system.